Pengaruh Strategi Pembelajaran Problem Solving Dan Inkuiri Dan Gaya Belajar Visual, Auditorial Terhadap Hasil Belajar Siswa - Lamsihar Gandauli Ritonga; Kms. Muhammad Amin Fauzi; Tian Abdul Aziz (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
The purpose of this study was to determine the effect of Problem Solving and Inquiry learning strategies and Visual Auditorial Learning Styles on the learning outcomes of fourth grade students of SDN 112238 Sepadan Jaya. The research method used was an experimental method using pre-test and post-test control group design. Hypothesis testing using two-way ANOVA test. The results of this study indicate that the sig. for the effect of the learning strategy is 0.00 so that Sig. <0.05. Then the results of the Fcount value 16.425> Ftable value 3.13, it can be concluded that there is an effect of Problem Solving and Inquiry learning strategies on student learning outcomes. For the sig. for the influence of learning styles amounted to 0,000; (0.000 <0.05) so that the Sig. <0.05; and the results of the value of Fcount 16,425 <Ftable96,654 so it can be concluded that there is an effect of learning styles on student learning outcomes. However, for the learning strategy * learning style, it can be seen that the value of F = 0.000 and the value of Sig. = 0.990. While the F-table value is 3,13; (0,000 <3,13) then Fcount <Ftable. Next look at the Sig. = 0.990; (0.990> 0.05). From the results of the F test and the Sig. It is concluded that H0 is accepted, that is, there is no simultaneous influence between learning strategies and student learning styles on student learning outcomes.